2018
DOI: 10.12693/aphyspola.134.1217
|View full text |Cite
|
Sign up to set email alerts
|

The Harrison Model as a Tool to Study Phase Transitions in Magnetocaloric Materials

Abstract: Modeling of hysteresis loops close to the Curie point may shed some light on physics of magnetization processes in magnetocaloric materials. In the present paper the model advanced by Harrison is used to describe magnetization curves of La(Fe,Co,Si)13 alloy. Systematic study has revealed that values of some model parameters depend significantly on temperature. The trends of their variations are discussed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The present contribution is inspired by an excellent review work published recently [5]. It extends several concepts which have been mentioned in the previous publications [6][7][8][9]. The fundamental concept of the paper is to modify the Harrison model of ferromagnetism to make it more useful for engineering purposes.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The present contribution is inspired by an excellent review work published recently [5]. It extends several concepts which have been mentioned in the previous publications [6][7][8][9]. The fundamental concept of the paper is to modify the Harrison model of ferromagnetism to make it more useful for engineering purposes.…”
Section: Introductionmentioning
confidence: 88%
“…the new vector quantity βm B can be called a "supermagneton". In this model the "supermagneton" is a new quantum particle, that is acted upon by the effective field" [6].…”
Section: A Brief Introduction To the Harrison Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplication by m and regrouping leads to the relationship g = t m 4 3 + (t − 1)m 2 − hm, which for a constant t value (t ∈ 0; 1 ) behaves qualitatively quite similarly to expression (1). The connection of the Harrison concept to the fundamental Landau theory was first elucidated in [25].…”
Section: The Harrison Model Versus Other Commonly Used Descriptions O...mentioning
confidence: 99%
“…Wall jumps create a change in magnetic flux and thus generate eddy currents that dissipate energy due to the Joule effect. Since temperature is a factor strongly affecting ferromagnetic material properties (study [1] showed the temperature effect on magnetization curves for special materials), describing the losses accurately is crucial [2,3].…”
Section: Introductionmentioning
confidence: 99%